Monday

October 20, 2014

October 20, 2014

Posted by **Kim** on Wednesday, March 14, 2007 at 10:33pm.

-4 < -3x-13 < 26

Add 13 to all three parts of the inequality.

9 < 3x < 39

Divide all three parts by 3.

3 < x < 13

The < signs should all be "less than or equal, but I can't type that symbol with this computer

Take it apart into 2 statements

a) -4<=-3x-13

3x<=-9

x<-3

AND

b)-3x-13<=26

-3x<=39

x>=-13

now combine it into -13<=x<=-3

or you could do it the way it sits

-4<=-3x-13<=26

add 13

9<=-3x<=39

divide by -3, remember to reverse the inequality sign

-9>=x>=-13

which is the same result as in my first solution.

drwls, you missed the -sign in front of the 3x.

**Answer this Question**

**Related Questions**

i lied. very quick calc problem. - f(x) = abs(sin(x)), -pi less than or equal to...

Algebra - If 1.2 is (less than or equal to) a (less than or equal to 5.1 and 3 (...

math - Identify the domain and range of the following: f(x) = 4-x^2, -5<x<...

Math - Tanker boats cannot be in the bay when the depth of water is less or ...

calc ii - if we know that 12 is less than or equal to f(x) which is less than or...

Statistics - Let Y be a random number between 0 and 1 generated by an idealized ...

ap stats - Continuous Random Variable, I Let X be a random number between 0 and ...

stats - Continuous Random Variable, I Let X be a random number between 0 and 1 ...

math - State the null hypothesis, Ho, and the alternative hypothesis, Ha, that ...

random variables - For the standard normal random variable Z, compute the ...